Heavy water (D2O) induces autophagy-dependent apoptotic cell death in non-small cell lung cancer A549 cells by generating reactive oxygen species (ROS) upon microtubule disruption - Das, Amlan; Chakrabarty, Subhendu; Nag, Debasish; Paul, Santanu; Ganguli, Arnab; Chakrabarti, Gopal (Toxicology in vitro, 2023)
Deuterium oxide (D2O) or heavy water is known to have diverse biological activities and have a few therapeutic applications due to its limited toxicity to human subjects. In the present study, we investigated the mechanism of D2O-induced cytotoxicity in non-small cell lung cancer A549 cells. We found that D2O-treatment resulted in cytotoxicity, cell cycle arrest, and apoptosis in A549 cells in a dose-dependent fashion. In contrast, limited cytotoxicity was observed in lung fibroblasts WI38 cells. Moreover, D2O-treatment resulted in the disruption of the cellular microtubule network, accompanied by the generation of ROS. On further investigation, we observed that the intracellular ROS triggered autophagic responses in D2O-treated cells, leading to apoptosis by inhibiting the oncogenic PI3K/ Akt/ mTOR signaling. D2O-treatment was also found to enhance the efficacy of paclitaxel in A549 cells. D2O induces autophagy-dependent apoptosis in A549 cells via ROS generation upon microtubule depolymerization and inhibition of PI3K/ Akt/ mTOR signaling. It augments the efficacy of other microtubule-targeting anticancer drug taxol, which indicates the potential therapeutic importance of D2O as an anticancer agent either alone or in combination with other chemotherapeutic drugs. [Display omitted] •D2O inhibits growth of Non-small cell lung carcinoma A549 cells.•D2O promotes ROS generation in A549 cells by disrupting cellular microtubules.•D2O induces autophagy dependent apoptosis by inhibiting PI3K/ Akt/ mTOR signaling.•D2O synergistically potentiates the efficacy of taxol in A549 cells.